Nutrition improvement program for rural compulsory education students and individual health - Liang, Yinhe; Chen, Xiyin; Zhao, Chenxiao; Jiang, Shaoxiang (Frontiers in Public Health, 2022)
We use the county-by-county rollout of the program and employ the difference-in-difference (DID) methodology to identify the effects of the implementation of the nutrition improvement program for rural compulsory education students on adolescent health. The results show that the nutrition improvement program reduces the frequency and probability of illness and improves the students' health status. The heterogeneity analysis indicates that the children in western regions and children left behind have a greater marginal improvement. It finds that the nutrition improvement program for rural compulsory education students improves adolescent health through diversifying nutrition intake to alleviate malnutrition and developmental delay in impoverished areas. The program can promote adolescent health in impoverished areas, which has a role in improving regional health disparities and alleviating the intergenerational entrenchment of poverty.